A study of temperature control in different designs of emergency drug transport bags. (3rd May 2019) - Dingley, J.; Thatcher, N.; Williams, D.
Summary: We investigated whether low melting point phase‐change waxes could be incorporated into emergency drug transport bags to attenuate the known temperature extremes their contents can be exposed to. We exposed two custom‐made hollow‐walled drug containers placed within a pair of drug transport bags to three day/night cycles including periods of direct radiant sunlight. The wall cavities of one contained air, whereas those of the other contained a paraffin wax (melting point of 44–46 °C) with a high latent heat of fusion (until fully melted, its temperature does not increase further). We collected 25, 920 temperature datasets at six locations. We found that 97.8% and 84.7% of ampoule temperatures within the wax and air cavity containers, respectively, were within a target range of 15–40 °C over the study duration (Levene statistic W = 4279.1; Levene's test for equality of variance, p < 0.001). Ampoule temperatures in the wax cavity container only exceeded 40 °C for 1.7% of the time. Even when they did so, their temperature was attenuated to 40.3 °C, despite an ambient air temperature of > 40 °C for 6.4% of the time (peak 46.9 °C) and a bag surface temperature of > 40 °C for 17.2% of the time (peak 64.4 °C). In contrast, the ampoule temperature in the air cavity container exceeded 40 °C for 17.1% of the time (peak 54.1 °C). The latent heat of fusion of phase‐change materials may be exploited in the design of drug transport bags to mitigate any temperature changes in the drugs stored within them.